Rekayasa Nilai dalam Tahap Reviu Perencanaan Konstruksi (Studi Kasus: Pelabuhan Perikanan Terintegrasi di PPN Pengembangan Bali) - Riyadi, Sugeng; Priyambodo, Bambang; Naibaho, Pio Ranap Tua; Sembiring, Kristina (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2026)
The ongoing construction of the project requires a fairly large allocation of funds, and it is necessary to reconsider whether the design used is optimal. This can be done by reviewing the project planning design so that it is possible to make cost savings by identifying and reducing unnecessary costs without reducing the level of quality, reliability and function of the project itself. Carrying out value engineering techniques, namely carrying out cost analyzes by comparing the costs per item with the details of each job from the contractor's offer to find the cheapest price up to the negotiation stage for cost savings and efficiency. The AHP (Analytic Hierarchy Process) method can be used as a solution to problems in finding decisions, and for assessment using a Likert scale questionnaire. Value engineering in the planning review by taking a case study of an ongoing project in the Pengambengan area of ​​Bali, namely the integrated fishing port project. There are 3 alternatives compared to the planning budget, namely breakdown analysis techniques (Work Breakdown Structure), cost modeling techniques (Cost modeling techniques), and Delphi techniques (Delphi Teqhnique). In value engineering, you can see the price comparison for each work item for planning reviews. The results for the final review based on value engineering RAB planning estimate Rp. 1,626,877,637,500. The stages in the AHP method analysis are determining the objective of the analysis, namely value engineering in selecting contractors, determining the analysis criteria: Cost Budget Plan, Detailed Drawings, Technical Specifications, and Implementation Time, as well as determining alternative options